Oestradiol Regulates Neuropeptide Y Release and Gene Coupling with the GABAergic and Glutamatergic Synapses in the Adult Female Rat Dentate Gyrus. (December 2015) - Velíšková, J.; Iacobas, D.; Iacobas, S.; Sidyelyeva, G.; Chachua, T.; Velíšek, L.
Abstract : Neuropeptide Y (NPY) is an endogenous modulator of neuronal activity affecting both GABAergic and glutamatergic transmission. Previously, we found that oestradiol modifies the number of NPY immunoreactive neurones in the hippocampal dentate gyrus. In the present study, we investigated which oestrogen receptor type is responsible for these changes in the number of NPY‐positive neurones. Furthermore, we determined the effects of oestrogen receptor activation on NPY release. Finally, we examined the contribution of oestrogen toward the remodelling of the GABAergic and glutamatergic gene networks in terms of coupling with Npy gene expression in ovariectomised rats. We found that activation of either oestrogen receptor type (ERα or ERβ) increases the number of NPY‐immunopositive neurones and enhances NPY release in the dentate gyrus. We also found that, compared to oestrogen‐lacking ovariectomised rats, oestrogen replacement increases the probability of synergistic/antagonistic coupling between the Npy and GABAergic synapse genes, whereas the glutamatergic synapse genes are less likely to be coupled with Npy under similar conditions. The data together suggest that oestrogens play a critical role in the regulation of NPY system activity and are also involved in the coupling/uncoupling of the Npy gene with the GABAergic and glutamatergic synapses in the female rat dentate gyrus.